Oxygen weaning after hospital discharge in children with bronchopulmonary dysplasia. Issue 11 (19th April 2016) - Yeh, Jennifer; McGrath‐Morrow, Sharon A.; Collaco, Joseph M.
Summary: Background: In the United States, approximately 12, 000 preterm infants are diagnosed with bronchopulmonary dysplasia (BPD) and many of these infants require supplemental oxygen after initial hospital discharge. In children with BPD we sought to identify factors associated with supplemental oxygen use after initial hospital discharge, factors associated with duration of supplemental oxygen use, and methods used to wean off supplemental oxygen in the home environment. Methods: All subjects (n = 420) with the diagnosis of BPD were recruited from a single center Bronchopulmonary Dysplasia Clinic between 2008 and 2013. Subject information was obtained from patient history records, patient demographics, and caregiver questionnaires. Results: Younger gestational age and having a Nissen fundoplication were associated with home supplemental oxygen use in subjects with BPD. Of the 154 subjects who received supplemental oxygen at home, 38% received flows ≤1/8 LPM, 30% received flows >1/8 LPM and ≤1/4 LPM, 21% received flows >1/4 LPM and ≤1/2 LPM, and 11% received flows >1/2 LPM. Among subjects receiving ≤1/8 LPM of oxygen, the median age of weaning off oxygen was 10.1 months, but increased depending on level of oxygen flow at initial outpatient visit. Of the 137 subjects weaned off of oxygen during the study period, weaning was not supervised by a physician in 32.1% of subjects. Conclusion: Home supplemental oxygen use is common in infants diagnosed with BPD. In this study, the median age of weaning off supplemental oxygen was 10.1 months after initial hospital discharge. Unsupervised weaning of supplemental oxygen occurred in 32.1% of subjects with BPD.Pediatr Pulmonol. 2016;51:1206–1211. © 2016 Wiley Periodicals, Inc.